2022
DOI: 10.1101/2022.03.28.22273010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 21L/BA.2-21K/BA.1 “MixOmicron” SARS-CoV-2 hybrid undetected by qPCR that screen for variant in routine diagnosis

Abstract: Among the multiple SARS-CoV-2 variants identified since summer 2020, several have co-circulated, creating opportunities for coinfections and potentially genetic recombinations that are common in coronaviruses. Viral recombinants are indeed beginning to be reported more frequently. Here, we describe a new SARS-CoV-2 recombinant genome that is mostly that of a Omicron 21L/BA.2 variant but with a 3-prime tip originating from a Omicron 21K/BA.1 variant. Two such genomes were obtained in our institute from adults s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Recently, an additional variant has been identified, generated from the recombination of the BA.1 and BA.2 subvariants, which has been found in patients co-infected with the two variants. However, the recombination site does not involve the epitope recognized by D3, suggesting that the mAb efficacy should not be compromised by this new emerging viral strain [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an additional variant has been identified, generated from the recombination of the BA.1 and BA.2 subvariants, which has been found in patients co-infected with the two variants. However, the recombination site does not involve the epitope recognized by D3, suggesting that the mAb efficacy should not be compromised by this new emerging viral strain [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colson et al in Marseille detected two samples with a recombinant genome that was mostly that of a BA.2 variant but with a 3 tip originating from BA.1 [88]. Gu et al in Japan reported two more cases with a breakpoint near the 5 end of the Spike gene (nucleotide position 20,055-21,618) [89].…”
Section: Ba1-ba2 Recombinantsmentioning
confidence: 99%
“…As expected for coronaviruses, multiple recombinants ( Focosi and Maggi, 2022 ) have been detected to date (designed by the PANGOLIN nomenclature with the “X” prefix and progressive alphabet letters, with one more letter added when the alphabet is over), with the left part of the description indicating the Spike donor lineage. The recombinants can be summarized as follows: DeltaxBA.1: XD (France and Denmark ( Zayet et al, 2022 )), XF (UK) DeltaxBA.1.1: XS (USA) BA.1xBA.2 ( Colson et al, 2022 ): XE (a.k.a. V-22APR-02 in PHE), XG (Denmark), XH (Denmark), XJ (Finland), XK (Belgium), XN (UK), XT (South Africa), XU (India), XV (Denmark and Italy), XW (USA, Germany, England), XY (USA), XAA (USA), XAB (Germany), XAC (Canada and USA), XAF (Costa Rica), XAG (Brazil), XAK (Germany), XAL (Germany), XAQ (Canada), XAR (Reunion) BA.1.1xBA.2: XM (Europe), XP (UK), XQ (UK), XR (UK), and XZ BA.1.1xBA.2.9: XAM (Panama and USA), XAU (Spain, England, France) BA.2xBA.1: XAD (Germany), XAE (USA, Chile), XAH (Slovenia), XAP (USA) BA.2.3.13xBA.1: XAT (Japan) BA.2xBA.4: BA.2.12.1xBA.4 (England) BA.2xBA.5: XAV (USA, Scotland) BA.2xBA.5.1: XAN (Spain, Denmark) BA.2.5xBA.5: XAZ (France, Germany, Croatia, Denmark and USA) BA.2.76xBA.5.2: (PANGO issue #896) BA.2xDelta: BA.2xAY.122x: XAW (Russia) BA.2xAY.45: XAY/C1 (South Africa) C2 BA.5xBA.2: XAS (USA) BA.2.75xBJ.1: XBB …”
Section: Co-infections and Recombinantsmentioning
confidence: 99%
“…BA.1xBA.2 ( Colson et al, 2022 ): XE (a.k.a. V-22APR-02 in PHE), XG (Denmark), XH (Denmark), XJ (Finland), XK (Belgium), XN (UK), XT (South Africa), XU (India), XV (Denmark and Italy), XW (USA, Germany, England), XY (USA), XAA (USA), XAB (Germany), XAC (Canada and USA), XAF (Costa Rica), XAG (Brazil), XAK (Germany), XAL (Germany), XAQ (Canada), XAR (Reunion) BA.1.1xBA.2: XM (Europe), XP (UK), XQ (UK), XR (UK), and XZ BA.1.1xBA.2.9: XAM (Panama and USA), XAU (Spain, England, France) …”
Section: Co-infections and Recombinantsmentioning
confidence: 99%